The Role of Bronfenbrenners Ecological Systems Theory in Enhancing Interpretive Consistency in Mixed Research (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
One of the nine major threats to legitimation (i.e., the degree that integration of findings leads to credible and defensible meta-inferences) is sample legitimation integration (Onwuegbuzie & Johnson, 2006). Addressing this form of legitimation requires the researcher to maintain interpretive consistency between the selected sampling design and the inferences made from the ensuing findings. To facilitate researchers efforts to address interpretive consistency, in this article, we provide a meta-sampling framework that is structured in accordance to the dimensions of Bronfenbrenners (1979) ecological systems model. In this meta-framework, the four dimensions of the model are juxtaposed to various types of generalizations, sampling-based considerations, and mixed sampling criteria. Application of this inclusive framework is appropriate for the conduct of quantitative, qualitative, and mixed research.